An unprecedented election : media, communication, and the electorate in the 2016 campaign /: media, communication, and the electorate in the 2016 campaign. (2018) - Warner, Benjamin R; Bystrom, Dianne G; McKinney, Mitchell S; Banwart, Mary C, 1968-
No abstract available